Effectiveness of Probiotics and Prebiotics Against Acute Liver Injury: A Meta-Analysis - Xu, Sheng; Zhao, Min; Wang, Qinjian; Xu, Zhihua; Pan, Binhui; Xue, Yilang; Dai, Zebin; Wang, Sisi; Xue, Zhanxiong; Wang, Fangyan; Xu, Changlong (Frontiers in Medicine, 2021)
Background and aims: Acute liver injury (ALI) is a clinical syndrome characterized by rapid loss of liver function, which may progress to life-threatening liver failure. We conducted this meta-analysis to examine the evidence on the effects of probiotics or prebiotics on ALI. Methods and results: Several databases, including PubMed, EMBASE, and Cochrane Library were scrutinized from the inception through February 2021 by combining key search terms, yielding 26 eligible studies, which concluded that modulation of gut microbiota significantly decreased aspartate transaminase (standardized mean differences (SMD) -1.51, 95% confidence interval (CI): -2.03 to -1.00), alanine aminotransferase (SMD -1.42, 95% CI: -1.85 to -0.98), and bilirubin (SMD -0.91, 95% CI: -1.33 to -0.49). In addition, administration of probiotics or prebiotics also promoted proliferation of Bifidobacterium (SMD 1.21, 95% CI: -0.18 to 2.60) and inhibited Enterococcus (SMD -1.00, 95% CI: -1.39 to -0.61), contributing to lower levels of endotoxin (SMD -2.14, 95% CI: -2.91 to -1.37). Tight junction protein ZO-1 (SMD 1.95, 95% CI: 0.14 to 3.76) was upregulated after intervention, thereby reducing bacterial translocation to the liver (odds ratio (OR) = 0.23, 95% CI: 0.13 to 0.44) and mesenteric lymph node (OR = 0.14, 95% CI: 0.08 to 0.26), with decreased TNF-α (SMD -2.84, 95% CI: -3.76 to -1.93) and IL-6 (SMD -2.62, 95% CI: -4.14 to -1.10). Oxidative stress was also relieved by reducing malondialdehyde (SMD -1.83, 95% CI: -2.55 to -1.10), while elevating superoxide dismutase (SMD 1.78, 95% CI: 1.00 to 2.55) and glutathione (SMD 1.83, 95% CI: 0.76 to 2.91). Conclusion: Our findings suggest that probiotics and prebiotics could be a promising therapeutic strategy in ALI and possess a potential for clinical applications.